Squamous Cell Carcinoma of the Skin: Epidemiology, Diagnosis, Management, Recurrence and Mortality Rates for the Bulgarian Population - Ivelina Yordanova; Preslav Vasilev; Milen Karaivanov; Martin Karamanliev; Dobromir Dimitrov; Petranka Troyanova (Journal of Biomedical & Clinical Research)
Squamous cell carcinoma of the skin (SCCs) accounts for 20-30% of non-melanoma skin cancers, resulting in 1 million cases in the United States annually. The risk of developing SCCs increases annually, and this process will likely be continued because of the aging population. We investigated 355 patients with histopathologically confirmed SCCs. We rated the age- and sex-related incidence, risk factors, localisation, pathological features, staging systems and treatment, and the recurrence and mortality rates of the tumours. Staging and risk stratification for recurrence and metastases is significant. Most SCCs are successfully treated surgically, with a small subset of carcinomas leading to recurrence, metastasis, and death. Patients with advanced and metastatic disease are often inappropriate for surgical and radiation therapy. We present the first study on squamous cell carcinoma of the skin conducted for the population of the Pleven and Lovech regions of Bulgaria.